IMF Participation in the Regulatory Oversight Committee of the Global Legal Entity Identifier System. (Policy Papers; Policy Paper ;, 2013)
This paper describes the Global Legal Entity Identifier (LEI) System and proposes Fund participation in the LEI Regulatory Oversight Committee (ROC) as an observer. An Executive Board decision is required for this purpose and is proposed in this document. The paper is organized as follows: - Part I describes the background to and governance structure of the Global LEI System. - Part II discusses the implications of Fund participation in the ROC as an observer. Part III sets out a proposed decision for Executive Board approval.